2008
DOI: 10.1007/s10765-008-0500-3
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Effective Thermal Conductivity of Dunite Rocks as a Function of Temperature

Abstract: The thermal conductivity, thermal diffusivity, and heat capacity per unit volume of dunite rocks taken from Chillas near Gilgit, Pakistan, have been measured simultaneously using the transient plane source technique. The temperature dependence of the thermal transport properties was studied in the temperature range from 303 K to 483 K. Different relations for the estimation of the thermal conductivity are applied. A proposed model for the prediction of the thermal conductivity as a function of temperature is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…are dumped into adjustable parameters and the errors in predicting thermal conductivity are only up to 10% in the temperature range 243 K to 333 K, which is the most interesting range for construction purposes. As far as the results of Eq.7 are concerned, these are fairly good at room temperature and above (with in 10%) [3]. But, this proposal is not recommended for the prediction of thermal conductivity in temperature range lower than the room temperature.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…are dumped into adjustable parameters and the errors in predicting thermal conductivity are only up to 10% in the temperature range 243 K to 333 K, which is the most interesting range for construction purposes. As far as the results of Eq.7 are concerned, these are fairly good at room temperature and above (with in 10%) [3]. But, this proposal is not recommended for the prediction of thermal conductivity in temperature range lower than the room temperature.…”
Section: Resultsmentioning
confidence: 94%
“…The density related properties of the selected samples at room temperature along with their thermal properties in temperature range (303-483 K) are already published [3]. In this paper only the thermal transport properties are measured in temperature range 83 to 303 K at normal pressure, with air as saturant in pore spaces, using Transient Plane Source Technique [4].…”
Section: Ultramaficmentioning
confidence: 99%
See 1 more Smart Citation
“…Beginning from the pioneer work of [3], the temperature-dependent thermal properties of geomaterials have been studied for a long time in relation with various engineering applications such as geothermal reservoirs, underground storage of nuclear waste or petroleum and natural gas geology. This subject is always in continuous progress with a remarkable number of results conducted on different types of soils and rocks in the last decade [2,4,[6][7][8][9]. A general tendency of decreasing of thermal conductivity as a function of temperature can be stated from these contributions.…”
Section: Variation Of the Effective Thermal Conductivity Of Geomaterimentioning
confidence: 99%
“…The study of the temperature dependence of thermal conductivity of porous medium like rocks and soils thas been intensively carried out in the last decade due to the large number of applications such as geothermal reservoirs, underground storage of nuclear waste, and petroleum and natural gas geology. Various researches conducted on different types of rocks, soils, and minerals have shown that the thermal conductivity of geomaterials decreases when the temperature increases [1][2][3][4][5][6][7][8][9][10][11] even if in some exceptional cases the conductivity slightly increases with temperature.…”
Section: Introductionmentioning
confidence: 99%